Pilot study of Qigong/Tai Chi Easy acute effects of meditative movement, breath focus and "flow" on blood pressure, mood and oxytocin in older adults - Linda K. Larkey; Taylor James; SeungYong Han; Dara L. James (Elsevier, 2023)
Background: Older adults are increasingly lonely and at risk for hypertension. Endogenous oxytocin levels are associated with lowering blood pressure (BP), suggesting value in increasing oxytocin. Regular practice of Tai Chi improves BP and mood; we explored a single session of Tai Chi Easy (TCE) with older adults and feasibility of measuring oxytocin as a key biomarker. Method: In a single-arm pre-post design pilot study, 21 older adults (age 55-80) with mild-moderate hypertension practiced a single session (50-min) TCE. BP, psychosocial measures, and saliva samples were collected pre/post to examine feasibility of acute measures of oxytocin and explore effect sizes of outcomes. Participants (N = 21; 19 % Latinx, 76.2 % female, mean age 66.76). Results: BP systolic: 138.43-134.86; diastolic 78.48-78.00 (p > .05; Cohen's d −0.23; −0.08 respectively). Total Mood Disturbance (TMD) and Connection (CN) improved [TMD mean pre 41.891 (SD=19.60) to post 35.00 (SD=10.21), p = .01; Cohen's d − 0.67); CN mean 7.85 (SD=2.01) to post 9.05 (SD=1.00), p = .01; Cohen's d 0.70]. Baseline oxytocin was positively correlated with baseline loneliness (N = 14, r = .599); pre/post oxytocin changes were negatively correlated with baseline loneliness (N = 14, r = −.585). BP decrease was associated with characteristics of the intervention: "flow" (coef=.=0.58N = 17) and meditative/breath focus (coef=−1.78; N = 17). Discussion/Conclusion: Medium to large effect sizes indicating change in mood and connection were found for this single session intervention. Knowing that Tai Chi improves BP when practiced over time, this TCE intervention shows promise for planning a fully powered, randomized controlled study of BP, mood and perceptions of connection in hypertensive older adults. Feasibility of assessing acute salivary oxytocin is less promising. Increase in oxytocin levels occurred for those less lonely, but declined for lonelier participants. With different responses based on baseline loneliness scores, no mean change in oxytocin levels was found. Seemingly unstable levels (possibly related to interaction with study staff) suggests the need for further testing in more controlled study designs. Finally, BP associations with meditative/breath focus and flow could be further explored in future study designs addressing mediation.